The feasibility of biology module based on Stim-HOTS models - Pramesti, Betty Novia; Sajidan, Sajidan; Dwiastuti, Sri; Setyaningsih, Eko (Jurnal Pendidikan Biologi Indonesia, 2019)
Based on the need’s analysis done, the empowerment of higher-order cognitive skills of the students in Surakarta was not optimal yet. This research addressed to determine and describe the feasibility of biology module which was arranged based on Stimulating Higher-Order Thinking Skills (Stim-HOTS) model. This Research and Development (R&D) involved six expert validators, including material validator, module development validator, language validator, learning instrument validator, and school practitioners. The results showed that the percentages of the module feasibility were between 83% and 98% which were categorized as very good. Based on the results of the analysis, it can be implied that the Stim-HOTS-based module can be used as learning resource.